Task decomposition and the high performance junior tennis serve - Reid, M.; Elliott, B.; Whiteside, D. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
To develop consistency in the toss placement and racket trajectory, coaches often decompose the serve and practise it in separate parts. This study compared the kinematics of the ball toss as part of the discrete serve skill and when the skill was decomposed. A 22 camera VICON MX motion analysis system, operating at 250 Hz, captured racket and ball kinematics of 5 elite junior players hitting flat first serves (FS) directed to the 'T' of the deuce service box and a ball toss (BT) drill where players were instructed to perform the decomposed skill as in the FS. Paired t-tests were used to assess within-group differences. Vertical displacement of ball zenith increased significantly (~20cm) during BT. Consistency in select racket and ball kinematics characterised the FS, while this appeared to decrease in BT.